استخدام الطالب الجامعي لتقنيات الإعلام الرقمي في العملية التعليمية (دراسة تطبيقية على عينة من طلاب جامعة سرت) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aimed to know the role of digital media in the educational process from the perspective of the university youth at the University of Sirte, and the researcher relied on the descriptive method. The study population consisted of university youth at Sirte University and the sample number reached (130). To collect the data, the researcher used the questionnaire template to measure the phenomenon that needed to be measured. The study reached a number of results, inclusive of; The respondents' use of digital media applications came at a rate of 82%, and Facebook ranked first in front of the rest of the social media applications, and the respondents' confirmed that digital media has become necessary in university studies, with a rate of 87%.
Keywords: Digital media; educational process; university youth